Adaptasi Program Kewirausahaan Usaha Mikro Kecil Menengah Dalam Mengentaskan Kemiskinan Oleh Badan Amil Zakat Nasional Kota Jambi - Rafi’i Rafi’i; Sucipto Sucipto; Maryani Maryani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The entrepreneurship adaptation program by BAZNAS Kota Jambi has shown its ability to adjust to field conditions, including through directives issued by the Mayor of Jambi. This study uses a descriptive qualitative method aiming to explore: the implementation of the adapted entrepreneurship program for MSMEs in alleviating poverty, the supporting factors, and how the program contributes to poverty reduction efforts. The findings indicate that BAZNAS Kota Jambi has distributed productive zakat funds through the "Jambi Kota Mandiri" program to mustahik in the form of business capital or sales goods. However, only 20% of total zakat funds are currently allocated for productive purposes, while 80% remain allocated to consumptive assistance. This is contrary to the recommendation from BAZNAS Central, which suggests that 70% of zakat funds should be used productively to support poverty alleviation. Supporting factors for successful entrepreneurship among mustahik include strong human resources, entrepreneurial soft skills, motivation, regulatory support from BAZNAS, and social capital. However, the absence of consistent monitoring and evaluation prevents assessing whether the program can sustainably transform mustahik into muzakki. Without proper follow-up, the program risks reverting to one-time consumptive assistance. Therefore, strategic improvements and oversight mechanisms are necessary to enhance the program’s effectiveness and sustainability.